ANALISIS PENERAPAN TOTAL PRODUCTIVE MAINTENANCE (TPM) PADA MESIN CNC DRILLING DI PT AMTEK PRECISION COMPONENTS BATAM - purba, Fader Oloan; Susanti, Elva (Computer Science and Industrial Engineering, 2022)
ABSTRACT PT. Amtek Precision Component Batam is a manufacturing company located in the Citra Buana III area, PT. Amtek Precision Component Batam is a manufacturing company located in the Citra Buana III area of ​​Batam City which produces hard disk drive components. The object of this research is the Brother TC-20A CNC drill machine at PT. Amtek Precision Components Batam. This study uses the OEE method, then measures the six big loss using Pareto diagrams and fishbone diagrams. The study was conducted in January-June 2022 from the results of the calculation of the highest OEE value in June 2022 of 72.48%, the lowest OEE value in January 2022 of 72.18% with an average OEE value of 72.24%. is below the world standard, which is 85%. The result of the calculation of the six big loss factor that causes low engine performance is the breakdown loss factor with a value of 32.83%. Based on the fishbone diagram on the Brother TC-20A CNC machine, there are four factors that cause failure, namely human factors, machines, methods and materials. For this reason, it is necessary to propose weekly scheduled maintenance improvements and carry out training to improve employee performance.